Valuing People: A Study of Human Resource Accounting in Organizational Settings (KASBIT Business Journal, 2026)
This qualitative study examines the role of Human Resource Accounting (HRA) within the organizational dynamics of the Pakistani banking sector, and recognizes human capital as an important driver for permanent success. Under the title "Discovery of Human Element", the research checks how the HRA acts as a connection point among the qualitative dimensions of the management of people and quantitative needs for financial reporting. While the growing belief in the strategic significance of human resources, the practical application of the HRA has been detected inadequate. By using intensive interview and thematic analysis, this study reveals the alleged benefits of underlying motivations, implementation challenges and adopting HRAs in selected Pakistani banks. Results introduces new dimensions to discourse, emphasizing the importance of human factor, identifies reference -specific drivers and obstacles, with a view to moral implications and proposed directions for future research. The results outline the influence of organizational culture and context in HRA practice and emphasize the importance of moral ideas in reporting of human capital. This research provides valuable insight to scholars and doctors with a view to strategic use of the HRA, and it performs basic tasks to detect the role of long -term effects for future studies, comparison across the sector and measurement of human capital.